PEMANFAATAN MEDIA GAME EDUKASI WORDWALL UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SDN 02 MADIUN LOR KOTA MADIUN - Bagas Satria Prakoso; Sri Lestari; Rita Rahmadhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Interest in learning is one of the things that needs to be built in students for successful learning. In fact, the interest in learning of class V students at SDN 02 Madiun Lor still needs to be increased. Researchers conducted Classroom Action Research (PTK) as an effort to create active, creative and innovative learning that can increase students' interest in learning Indonesian through the use of wordwall educational game media in learning. PTK is carried out in two cycles. Each cycle consists of planning, action, observation and reflection activities. The results of the research show that the use of wordwall educational games media can increase the learning interest of class V students at SDN 02 Madiun Lor as indicated by an increase in the percentage of students fulfilling the indicators of learning interest. The increase in student interest in learning can be seen based on the results of the analysis of the observation sheet on student interest in learning in the pre-cycle. The results showed that the percentage of student learning completion was 40% of the total number of students who completed 4 out of 10 students were in the poor category, then the percentage of 60% was in the good category in cycle I, 90% in cycle II was in the very good category. The conclusion is that by using the wordwall educational game media, it can improve students' learning outcomes in learning, create interest in the material, so that students can more easily master lessons, and using wordwall will make it easier for teachers to deliver the material.